Constitutional oath of judges: a comparison with Australia, UK, US, and India - Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha; Ahmad, Muhamad Hassan (2021)
The written record of a judiciary oath can be traced as way back as ancient Greece, from Homer to Hesiod to Plate and it was more often than not associated with perjury . Hence oath was seen to be more closely related in law than religion. St Thomas Aquinas stated that “an oath is a reverence for the name of God is taken in confirmation of a promise. Hence what is confirmed by oath does not, for this reason, become an act of religion